2020
DOI: 10.2147/jbm.s237317
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Peripheral Blood Parameters of Pulmonary Tuberculosis Patients at St. Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia: Comparative Study</p>

Abstract: Background and Aim: Pulmonary tuberculosis is still among the leading cause of morbidity and mortality in Ethiopia. Different hematological abnormalities are commonly associated with pulmonary tuberculosis even though inconsistent results have been described. Hence, this study aimed to evaluate the hematological parameters of pulmonary tuberculosis patients visited St. Paul's hospital millennium medical college, Addis Ababa, Ethiopia. Methods: From April to September 2018, a comparative cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 16 publications
6
23
0
2
Order By: Relevance
“…There was a significant thrombocytosis in TB infected group which is in accordance with the study by Rathod et al (2017) who speculated the potential use of thrombocyte count as a marker for TB and found that 75 per cent of the TB infected patients had thrombocytosis. The ESR values obtained from the study had significant difference with that of healthy controls which is in agreement with the previously published studies (Oliva et al, 2008;Rohini et al, 2016;Kahase et al, 2020). Mandal and Chaven (2016) suggested that the increment in the ESR values were a common observation in active TB cases.…”
Section: Resultssupporting
confidence: 91%
“…There was a significant thrombocytosis in TB infected group which is in accordance with the study by Rathod et al (2017) who speculated the potential use of thrombocyte count as a marker for TB and found that 75 per cent of the TB infected patients had thrombocytosis. The ESR values obtained from the study had significant difference with that of healthy controls which is in agreement with the previously published studies (Oliva et al, 2008;Rohini et al, 2016;Kahase et al, 2020). Mandal and Chaven (2016) suggested that the increment in the ESR values were a common observation in active TB cases.…”
Section: Resultssupporting
confidence: 91%
“…Similar results with our findings about WBC have previously reported that anti-TB chemotherapy can reverse WBC count that is increased in PTB subjects due to the elevated count of polymorphonuclear leukocytes and macrophages during bacterial infection [ 40 , 43 , 44 ]. However, other studies have shown no statistically significant difference on WBC count before initiation and after the completion of intensive phase of treatment [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, there are reports that documented a significantly higher platelet count in the PTB than the control groups while others showed a significant decrement of platelet count which was explained by the early diagnosis of patients [ 43 ]. Notably, it seems that the anti-inflammatory effect of the platelets during TB infection is triggered both by inducing platelet-leukocyte crosstalk and the platelet induced shift to a more anti-inflammatory response [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haematological parameters like WBC count, platelet count, RBC count, haemoglobin and erythrocyte sedimentation rate are often seen altered in tuberculosis patients [43-46]. In our study, the blood profile of all the TB patients including those suspected for amyloidosis (Table 2) also reflected similar alteration in these inflammatory markers.…”
Section: Resultssupporting
confidence: 74%